Selection and identification of a bacterial community able to degrade and detoxify m-nitrophenol in continuous biofilm reactors - González, Ana Julieta (2015)
Nitroaromatics are widely used for industrial purposes and constitute a group of compounds of environmental concern because of their persistence and toxic properties. Biological processes used for decontamination of nitroaromatic-polluted sources have then attracted worldwide attention. In the present investigation m-nitrophenol (MNP) biodegradation was studied in batch and continuous reactors. A bacterial community able to degrade the compound was first selected from a polluted freshwater stream and the isolates were identified by the analysis of the 16S rRNA gene sequence. The bacterial community was then used in biodegradation assays. Batch experiments were conducted in a 2L aerobic microfermentor at 28°C and with agitation (200rpm). The influence of abiotic factors in the biodegradation process in batch reactors, such as initial concentration of the compound and initial pH of the medium, was also studied. Continuous degradation of MNP was performed in an aerobic up-flow fixed-bed biofilm reactor. The biodegradation process was evaluated by determining MNP and ammonium concentrations and chemical oxygen demand (COD). Detoxification was assessed by Vibrio fischeri and Pseudokirchneriella subcapitata toxicity tests. Under batch conditions the bacterial community was able to degrade 0.72mM of MNP in 32h, with efficiencies higher than 99.9% and 89.0% of MNP and COD removals respectively and with concomitant release of ammonium. When the initial MNP concentration increased to 1.08 and 1.44mM MNP the biodegradation process was accomplished in 40 and 44h, respectively. No biodegradation of the compound was observed at higher concentrations. The community was also able to degrade 0.72mM of the compound at pH 5, 7 and 9. In the continuous process biodegradation efficiency reached 99.5% and 96.8% of MNP and COD removal respectively. The maximum MNP removal rate was 37.9gm-3day-1. Toxicity was not detected after the biodegradation process.